2006
DOI: 10.1074/jbc.m512378200
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphoinositide 3-Kinase-AKT-Nitric Oxide-cGMP Signaling Pathway in Stimulating Platelet Secretion and Aggregation

Abstract: Phosphoinositide 3-kinase (PI3K) and Akt play important roles in platelet activation. However, the downstream mechanisms mediating their functions are unclear. We have recently shown that nitric-oxide (NO) synthase 3 and cGMP-dependent protein kinase stimulate platelet secretion and aggregation. Here we show that PI3K-mediated Akt activation plays an important role in agoniststimulated platelet NO synthesis and cGMP elevation. Agonist-induced elevation of NO and cGMP was inhibited by Akt inhibitors and reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
112
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(121 citation statements)
references
References 32 publications
8
112
1
Order By: Relevance
“…In platelets, it has been known for many years that high concentrations of NO donors (micromolar range) inhibit platelet function (35,36). However, we have shown recently that low concentrations of NO (low nanomolar range) stimulate platelet activation via the cGMPdependent protein kinase pathway, again indicating a biphasic effect of the NO-cGMP pathway in platelet activation (12,13,27,37). It is important to note that the controversy on the role of NO in platelets has been complicated by the fact that investigators in some studies used platelet preparations that are desensitized and thus no longer responsive to low concentrations of agonists (such as 0.1 unit/ml thrombin) (38).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In platelets, it has been known for many years that high concentrations of NO donors (micromolar range) inhibit platelet function (35,36). However, we have shown recently that low concentrations of NO (low nanomolar range) stimulate platelet activation via the cGMPdependent protein kinase pathway, again indicating a biphasic effect of the NO-cGMP pathway in platelet activation (12,13,27,37). It is important to note that the controversy on the role of NO in platelets has been complicated by the fact that investigators in some studies used platelet preparations that are desensitized and thus no longer responsive to low concentrations of agonists (such as 0.1 unit/ml thrombin) (38).…”
Section: Discussionmentioning
confidence: 89%
“…Agonist-activated platelets generate NO (10,11). We have recently shown that platelet agonists induce activation of phosphoinositide 3-kinase and Akt, which activates eNOS (12) and that eNOS plays an important role in NO synthesis during platelet activation and in stimulating cyclic guanosine monophosphate (cGMP)-dependent platelet secretion and secretion-dependent platelet aggregation (13,14). Here, we show that NO synthesis during platelet activation not only involves eNOS, but is also mediated by the constitutively expressed platelet iNOS.…”
mentioning
confidence: 99%
“…It was previously shown that phosphorylation of Akt and/or ERK plays a critical role in platelet function,60, 61, 62 and supports thrombus formation 63, 64. Thus, we examined whether e‐cigarettes exert any effect on these 2 markers of platelet activation.…”
Section: Resultsmentioning
confidence: 96%
“…PI3K has been observed to promote Akt activation during platelet stimulation [16,25], and two different isoforms of Akt, Akt1/PKBα and Akt2/PKBβ, have been found to play a role in platelet activation [3]. Once phosphorylated, Akt is known to phosphorylate and activate in its turn other proteins, including eNOS [9].…”
Section: Discussionmentioning
confidence: 99%